Measuring economic lifestyle and flows across population age groups: Data and methods in the application of the National Transfer Account (NTA) in the Philippines - J.M. Ian S. Salas; Rachel H. Racelis (Philippine Institute for Development Studies (PIDS), 2007)
This paper provides an overview of the National Transfer Accounts (NTA) system and then describes the methods and data used in the application of NTA in the Philippines. The NTA system is consistent with the System of National Accounts. It provides methodologies for assigning labor earnings and consumption to population age groups, and for estimating reallocation or transfer of economic resources across age groups. Age reallocations are generally from the working age groups to children and the elderly. Data sources for the estimation of components of the NTA Flow Accounts for the Philippines include National Income Accounts, National Health Accounts, National Education Expenditure Accounts, household income and expenditure surveys, and government finance documents. Some Philippine NTA results are presented as examples, specifically the age profiles of current consumption (C), labor income (YL), and the lifecycle deficit (LCD).
Keywords: 330; National Transfer Accounts; economic lifecycle; intergenerational transfer; income age profile; consumption age profile; lifecycle deficit; Bevölkerungsentwicklung; Alternde Bevölkerung; Generationengerechtigkeit; Öffentliche Sozialleistungen; Messung; Philippinen